Role of Peroral Endoscopic Myotomy (POEM) in the Management of Esophageal Diverticula - Bogdan P. Miutescu; Sarah Khan; Shruti Mony; Mouen A. Khashab (Korean Society of Gastrointestinal Endoscopy, 2020)
Esophageal diverticula are uncommon; however, when present, they can cause symptoms of dysphagia, regurgitation, and chest pain. Based on location and pathophysiological characteristics, they are classified as pulsion- and traction-type diverticula. In the past, the open surgical approach was the only treatment available; however, in the past few decades, transoral incisionless approaches in the form of rigid and flexible endoscopy have gained popularity. Diverticular peroral endoscopic myotomy has emerged as an alternative treatment option. In this paper, we reviewed the role of peroral endoscopic myotomy as a treatment option for different types of esophageal diverticula. Although a safe and effective procedure, this novel submucosal tunneling technique for the treatment of esophageal diverticula requires further validation, and head-to-head comparisons between the different approaches for the treatment of esophageal diverticula are warranted.